Effects of microcystin-containing cyanobacterial extract on hematological and biochemical parameters of common carp (Cyprinus carpio L.) - Sieroslawska, Anna; Rymuszka, Anna; Velisek, Josef; Pawlik-Skowrońska, Barbara; Svobodova, Zdenka; Skowroński, Tadeusz (Fish physiology and biochemistry, 2012)
The aim of the study was to assess the effects of a cyanobacterial extract containing microcystins (MCs) on selected hematological and biochemical parameters in common carp (Cyprinus carpio L.), as well as to determine the accumulation of toxins in fish tissues. The fish were immersed for 5 days in water containing toxins at a final concentration of 12 μg/L of microcystin LR equivalent. Microcystin LR residues were detected in fish liver, reaching 207, 238 and 260 ng/g f.w. of the tissues taken 24 h, 72 h and 5 days after the end of intoxication, respectively. The most substantial changes were found in fish plasma, including increases in creatine kinase, lactate dehydrogenase, ammonia, glucose, aspartate aminotransferase and alanine aminotransferase levels. A decline of about 50% in lysozyme activity was observed by the end of the experimental period. Moreover, a marked increase in ceruloplasmin activity was detected 24 h after the end of intoxication with a subsequent decrease in its activity after 72 h and 5 days. This study concludes that not only consumption of food containing toxins but also MCs dissolved in water may pose a threat to fish health. Additionally, detected changes in lysozyme and ceruloplasmin activity may have distinct effects in fish resistance against pathogens or oxidative stress, which should be taken into account in the future studies.
Keywords: Muramidase; přirozená imunita; Ceruloplasmin; ceruloplasmin; Carps; kapři; zvířata; testy toxicity; Microcystins; muramidasa; mikrocystiny; Immunity, Innate; Toxicity Tests; Microcystis; Animals